Evaluation of suicidal thoughts based on substance abuse and social support in soldiers - M Nosratabadi; P Dabbaghi (فصلنامه ابن سینا)
Abstract Background: Military service is a critical period in life of youth. In this period, exposure to anxiety factors causes to increase psycho-social context formation such as suicidal thoughts and drug abuse. The purpose of this study was to evaluate the suicidal thoughts based on drug abuse and social support variables among soldiers of AJA University of Medical Sciences. Materials and methods: In this correlation-based structural modeling study, 176 soldiers were selected using stratified random sampling. The data were gathered by three questionnaires including social support scale, beck scale for suicide ideation, and possibility of substance abuse scale Results: Totally, 28.4% of the studied individual were at high risk for suicidal thoughts (score above 10). There was inverse correlation between social support and social ideation (P<0.05). The structural model showed that 69% of the overall variance of suicidal ideation was attributed to social support and substance abuse. Conclusion: According to results, it can be concluded that the risk of suicidal is relatively high in soldiers of the AJA University of Medical Sciences this requires serious action by the authorities and other relevant organizations in order to improve the psychosocial health of soldiers.